2020
DOI: 10.3390/sports8070095
|View full text |Cite
|
Sign up to set email alerts
|

Verifying Physiological and Biomechanical Parameters during Continuous Swimming at Speed Corresponding to Lactate Threshold

Abstract: The purpose of this study was to verify the physiological responses and biomechanical parameters measured during 30 min of continuous swimming (T30) at intensity corresponding to lactate threshold previously calculated by an intermittent progressively increasing speed test (7 × 200 m). Fourteen competitive swimmers (18.0 (2.5) years, 67.5 (8.8) kg, 174.5 (7.7) cm) performed a 7 × 200 m front crawl test. Blood lactate concentration (BL) and oxygen uptake (VO2) were determined after each 200 m repetition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…In this case, the slope of the straight line may be greater, and the maximal perpendicular distance from the lactate curve may correspond to a higher point of the speed vs. lactate concentration curve, with a higher predicted lactate concentration as a result. A similar disa-greement between BL corresponding to LT compared to MLSS has been previously reported using LT F and LT int methods in adult swimmers [10,24]. Indeed, this is also confirmed in the current study between LT F and MLSS methods in children and adolescents.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this case, the slope of the straight line may be greater, and the maximal perpendicular distance from the lactate curve may correspond to a higher point of the speed vs. lactate concentration curve, with a higher predicted lactate concentration as a result. A similar disa-greement between BL corresponding to LT compared to MLSS has been previously reported using LT F and LT int methods in adult swimmers [10,24]. Indeed, this is also confirmed in the current study between LT F and MLSS methods in children and adolescents.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the participants in most of the cycling or running studies investigating the comparison of LT calculation methods are "healthy" [21], "moderately-trained" [15], or at a non-defined competitive level [13,36]. Well-trained swimmers participated in the current study and previous studies with swimmers [4,24,37]. The competitive level of participants may affect the physiological responses, altering the exercise intensity versus lactate concentration curve and all subsequent calculations for LT and sLT [3,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the anaerobic capacity in training, the capillary blood test was used for measuring the blood lactate (mmol L −1 ) and blood glucose (mmol L −1 ) before effort and after effort, when the 8x100 m specialized swimming stroke was used (motor test-MT1), start at 150 s, with a pause of 1 min approximately; the competition events were split 2x50 m (MT2), with 5 s pause; in the 5th and 15th minute after effort for the assessment of the quality of the recovery capacity after effort. The Lactate Pro portable analyzer with Lactate Pro Test Strips was used to determine the blood lactate, which was generally less than +/-2.0 mM over the physiological range of 1.0-18.0 mM (range of mean difference: −0.06 mM to 0.52 mM), Mean Squared Error and correction for Bias indicated that both the Edge and Xpress had low 'total' error (∼0-2 mM) for lactate concentrations <15 mM (e.g., Bonaventura et al, 2015); the blood glucose was determined by means of the portable analyzer Accu-Chek Performa Nano glucometer with Accu-Chek Performa test strips, Detection limit (lowest value displayed): 10 mg/dL (0.6 mmol/L) for the test strip, System measurement range: 10-600 mg/dL (0.6-33.3 mmol/L), Sample size: 0.6 µL, Test time: 5 s (Salgau, 2017;Ferreira et al, 2019;Arsoniadis et al, 2020a;Arsoniadis et al, 2020b). The time in the motor tests was measured with the help of the Professional Timer Stopwatch, Digital Sports Stopwatch with Countdown Timer, 100 Lap Memory, 0.001 Second Timing (water resistant, multi-functional stopwatch for swimming, running, training).…”
Section: Methodsmentioning
confidence: 99%
“…The anaerobic threshold tests measure the concentration of lactate in timed repetitions series, swimming at progressive speeds. The lactate concentration depending on the swimming speed shows the results of one of the most used blood tests (Bitang & Dulceanu, 2014;Nikitakis et al, 2019;Arsoniadis et al, 2020a;Arsoniadis et al, 2020b).…”
Section: Rho Variables Stage 4 (E4)mentioning
confidence: 99%